EUROPAMOBIL: A Vehicle for the European Union to Keep Moving - Charisi, Michaela (HAPSc Policy Briefs Series, 2022)
The purpose of this paper is to highlight the necessity to increase the connection the European youth has with the European Union. Education policy might be a responsibility of the Member States, but the EU shall take upon more initiatives in order to bring the young Europeans closer to it. EUROPAMOBIL, is a project that can add educational value to the currently covered areas by the European school curricula, without intervening on national territories and can have a positive impact among the youth, which is an interval part for the continuation of the EU and the achievement of its goals.